The Tiroca Model of PT Goto Gojek Tokopedia Tbk - Lysandra Priscilla; Alvi Diani Khoirunissa; Popy Rufaidah (Management Analysis Journal, 2023)
This research aims to analyze the strategy of PT GoTo Gojek Tokopedia Tbk. by using the TIROCA model (Tangible, Intangible Resources, and Organizational Capabilities Analysis) as a basis for identifying the company's strengths and weaknesses. This research uses the qualitative research method with a case study approach to explore the company's strategic strengths and weaknesses through tangible assets, intangible assets, and organizational capabilities. The results showed that the company's sustainable competitive advantage comes from technology as a tangible resource, brand reputation as an intangible resource, and the company's ability to manage product development and improve the quality of human resources as an organizational resource capability. This research contributes to expanding the understanding of PT GoTo's business strategy and provides advice for making the right decisions in developing the business in the future.